Group Decision Support System Based on Enhanced AHP for Tender Evaluation - Fadhilah, Ahmad; Wan Suryani, Wan Awang; Zarina, Mohamad; Fatma Susilawati, Mohamad (2014)
Application of model base in group decision making that makes up a Group Decision Support System (GDSS) is of paramount importance. Analytic Hierarchy Process (AHP) is the multi-criteria decision making (MCDM) that has been applied in GDSS. In order to be effectively used in GDSS, AHP needs to be customized so that it is more user friendly with ease of used features. In this paper, we propose an enhanced AHP model for GDSS tendering. The enhanced AHP method used is the Guided Ranked AHP (GRAHP). It is a technique where decision matrix tables are automatically filled in based on ranked data. However, the generated values in the decision matrix tables can still be altered by following the guidelines which in turn serve the purpose of improving the consistency of the decision matrix table. This process is transparent to Decision Makers because the degree of data inconsistency is visible. A prototype system based on tendering process has been developed to test the GRAHP model in terms of its applicability and robustness.